Career readiness in deaf and hard-of-hearing high school students in special education - Gorodilova, Svetlana; Shakirova, Oksana; Krasavina, Yulia (Specijalna edukacija i rehabilitacija, 2026)
Introduction. A successful career is one of the key factors that ensure meaningful social integration for people with disabilities. Considering that career choices are made by adolescents immediately after graduation from high school, it is vital that special schools’ career guidance programs effectively address typical challenges for each type of disability. Objectives. The aim of this study was to examine career readiness in deaf and hard-of-hearing (DHH) high school students educated in special schools in Russia and reveal gaps and specific challenges that could be addressed through tailored guidance programs. Methods. Two studies on career readiness were conducted, involving a total of 410 participants, including DHH high school students (N = 205) and high school students without hearing impairment (N = 205). Results. Findings indicated statistically reliable differences in career readiness, intensity of career preferences, and range of professional domains of interest between DHH students and their hearing peers. Qualitative results supported earlier observations about the vulnerable position of young DHH people in making career choices. Conclusion. The identified challenges in career readiness among DHH high school students allowed us to justify urgent directions for their career guidance, including self-awareness, awareness of professional domain and labor market, and the ability to align individual health issues with occupational demands.